2018
DOI: 10.1002/cjas.1486
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour‐Based and Outcome‐Based Control Systems: A Meta‐Analytic Study

Abstract: Sales control systems are instruments used by firms to improve performance and other organizational outcomes. To understand their antecedents and consequences, this paper conducts a meta-analysis based on 104 studies. The results showed significant relationships between behaviour-and outcome-based control systems and the complexity of the products, bonuses, financial performance, sales innovation, organizational support and satisfaction with supervisors. The outcomes revealed that behaviour-based control syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…From the positive view, previous researchers argued that under behavior-based control, salespersons are likely to get the chance to communicate with their managers more frequently, and managers will thus get more information about salespersons' effort during the selling process and provide feedback to improve salespersons' selling skills. This will increase the salesperson's trust in the organization and satisfaction towards the job [30,31]. On the other hand, the negative view argues that since behavior control requires frequent evaluation and top-down determination of routine activities, salesperson will develop negative feelings and senses of disgust towards their managers [32].…”
Section: Sales Control Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the positive view, previous researchers argued that under behavior-based control, salespersons are likely to get the chance to communicate with their managers more frequently, and managers will thus get more information about salespersons' effort during the selling process and provide feedback to improve salespersons' selling skills. This will increase the salesperson's trust in the organization and satisfaction towards the job [30,31]. On the other hand, the negative view argues that since behavior control requires frequent evaluation and top-down determination of routine activities, salesperson will develop negative feelings and senses of disgust towards their managers [32].…”
Section: Sales Control Systemsmentioning
confidence: 99%
“…Whereas capability controls emphasize the development of sales-related knowledge and skills, which involves managers' active efforts in setting capability goals, training, and providing diagnostic feedback. However, some later studies, e.g., [9,17], including the latest meta-analysis studies [31], still treated behavior control as an uni-dimensional construct instead of splitting it into capability control and activity control, which might lead to confusing conclusions.…”
Section: Sales Control Systemsmentioning
confidence: 99%
“…The results of the supplementary analyses revealed that the joint use of output and behavioral feedback was not helpful for CSB, which is inconsistent with findings denoting a synergistic interplay between the two types of feedback (de Oliveira Santini et al, 2019;Kim, 1984;Miao and Evans, 2013). Scholars highlight that it is beneficial to implement both output and behavioral feedback because they can offset the drawbacks of each feedback (de Oliveira Santini et al, 2019;Evans, 2013, 2014). Distinct from this line of work, we found that the mixture of output and behavioral feedback did not play an additive role in predicting CSB.…”
Section: Theoretical Implicationsmentioning
confidence: 88%
“…Salespeople's compensation is determined by output standards (Rijsdijk and van den Ende, 2011), with rewards depending on incentives (Piercy et al, 2012). Output feedback signals that salespeople are evaluated only in terms of sales, market share and profit contribution (de Oliveira Santini et al, 2019;Samaraweera and Gelb, 2015), which causes them to take responsibility for their sales performance. As the risks for meeting sales objectives shift from the firm to salespeople under an output feedback system (Anderson and Oliver, 1987), salespeople recognize the importance and meaning of their sales performance, thereby striving to engage in behaviors that are instrumental for the desired end results.…”
Section: Ejm 572mentioning
confidence: 99%
See 1 more Smart Citation